Writing as a Skill of Learning English in Bangladesh Education System Perspective - Akter, Ferdousi (International Journal of Applied and Scientific Research, 2024)
This paper investigates the role of writing as a learning skill in Bangladesh's English education. It assesses writing instruction across primary, secondary, higher secondary, and tertiary levels, focusing on English textbooks by NCTB, class schedules at Willes Little Flower School and Dhaka City College, and question papers from SSC-2017 and HSC-2018. Data from Bangladesh Education Statistics 2017 highlights the shortage of senior teachers in universities. Through this analysis and reference to scholarly works, it underscores the significance of writing as a vital component of English language acquisition within Bangladesh's educational framework. The paper concludes with recommendations for improvement.